Models of Religious Conflict Resolution in Multicultural Societies - Didik Suwarno; Kholid Mawardi (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Religious conflicts occur because of differences in concepts carried out by the followers of the religion itself. The emergence of judgments from one group to another usually triggers religious conflicts. This research is qualitative research, that is library research using data sources in the form of reference books and scientific journal articles. The results of this study provide three models for resolving religious conflicts, namely: 1. Handling strength-based social conflicts. 2. Handling socio-religious conflicts on a rights-based basis rests on the superiority of the rights of one party over the rights of others. 3. Handling is based on importance. As an Indonesian nation respects differences, builds mutual care, tolerance, because Indonesia is a big country that has many tribes, cultures, and religions. If we do not build mutual care, tolerance and respect for differences, it will be difficult to maintain the unity and unity of Indonesia.